Professionally-Directed Teaching as a Component of Forming Competent Specialist - Trishkina, Nina (Pedagogical Discourse, 2015)
The essence of professionally directed learning in high school is analyzed in the article. Modern approaches to the formation of professional competence while forming the future expert are identified. The professional competencies of trade and economic experts are characterized. Social and professional orientation, culture of thinking and temperament are the factors that determine the level of professionalism display. The definition of professional competence is regarded as the mastery degree of knowledge, skills and way of life as a system of communication skills that are required to perform the activity, but the professional competence – as the individual’s capacity to solve various professional tasks at different levels. The professional competence of trade and economics students is seen as a generalized personality trait that has four levels of development: low, medium, sufficient and high. The objectives, functions and results of professional activity are distinguished. The model of the competent professional forming considering professionally directed learning is developed.